Developing Distributorless Ignition System Learning Media for Automotive Engineering Students - Sudarwanto Sudarwanto; Tafakur Tafakur (Universitas Sarjanawiyata Tamansiswa, 2019)
This study aims to: (1) develop a learning media for practicing Distributorless Ignition (DLI) system for automotive engineering students and (2) identify the feasibility of the learning media for practical purpose in the classroom activities. The procedures of this research and development (RnD) study refers to the steps of product development by Borg and Gall (2007). A questionnaire was utilized to measure the learning media feasibility. Furthermore, there were media experts, content experts, and students as the user participated to evaluate and give feedback for the learning media improvement during the product development. The results reveal that (1) the distributorless ignition system learning media displays a systematic arrangement of the DLI components on acrylic boards accompanied by symbols of electrical components and (2) the product developed was suitable to facilitate studentsâ€™ learning activity.Â The content and media experts scored the learning media as very feasible (7.59 & 7.06), the average score of the response of small class users was 6.14 (feasible), and the scores of large class respondents were 6.80 (very decent). It can be concluded that the DLI learning media can be used to support the instructional activity for ignition system.